(untitled) - Murphy, James D. (New Jersey, 2014)
Courage to Execute will help you develop effective leadership skills and build high-performance teams that out-compete your rivals every time.
Keywords: Leadership,Success in business,Sự quản lý,Sự quản lý,Sự quản lý,Sự quản lý,Sự lãnh đạo,Thành công trong kinh doanh,Management